2002
DOI: 10.1074/jbc.m200231200
|View full text |Cite
|
Sign up to set email alerts
|

Desaturation and Hydroxylation

Abstract: Exchanging the identity of amino acids at four key locations within the Arabidopsis thaliana oleate desaturase (FAD2) and the Lesquerella fendleri hydroxylase/ desaturase (LFAH) was shown to influence partitioning between desaturation and hydroxylation (Broun, P., Shanklin, J., Whittle, E., and Somerville, C. (1998) Science 282, 1315-1317). We report that four analogous substitutions in the FAD2 sequence by their equivalents from the castor oleate hydroxylase result in hydroxy fatty acid accumulation in A. tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(74 citation statements)
references
References 38 publications
6
64
0
4
Order By: Relevance
“…Changes to an enzyme's regiospecificity typically require between two and six specific changes at key locations along the amino acid chain that occur over many generations (35,36). To accumulate mutations at these key sites, many additional mutations also accumulate, which tend to degrade attributes such as stability and turnover of the enzyme (37).…”
Section: Resultsmentioning
confidence: 99%
“…Changes to an enzyme's regiospecificity typically require between two and six specific changes at key locations along the amino acid chain that occur over many generations (35,36). To accumulate mutations at these key sites, many additional mutations also accumulate, which tend to degrade attributes such as stability and turnover of the enzyme (37).…”
Section: Resultsmentioning
confidence: 99%
“…Although it has previously been shown that desaturases can have additional functionality, such as acting as conjugases (25) or hydroxylases (26), different positional specificities depending on the type of lipid to which the substrate is conjugated (27), the chain length of the acyl group (28), or the ability of a soluble desaturase enzyme to catalyze two double bonds (⌬4 and ⌬9) into a saturated fatty acyl-ACP substrate (29), the ability of a desaturase enzyme to catalyze two double bonds (⌬12 and 3) on the same acyl chain (C18) has not previously been reported. It will be interesting to study how these ⌬12͞ 3 enzymes exert their dual positional specificity, because the regioselectivity of ⌬12 and 3 desaturases is Јv ϩ 3Ј (i.e., three carbons away from an existing double bond) and Ϫ3 (i.e., three carbons from the methyl end), respectively (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Eight highly conserved histidine residues have been shown to be required for function with the exception of one that is replaced by glutamine in some "front-end" desaturases, which introduce double bonds near C-1 in the substrate (3,31). Shanklin and colleagues (32) have identified a number of individual amino acids that are important for the chemoselectivity of the FAD2-like enzymes, which tend to have both desaturase and hydroxylase activities to varying degrees. A domain swapping study was undertaken by Napier and colleagues (33) to investigate the regioselectivity and substrate specificity of two front-end desaturases.…”
Section: Discussionmentioning
confidence: 99%